Decoración de interíores de oficinas usando realidad virtual - Montesdeoca B, Luis (2011)
The purpose of our application is to decorate the interiors of offices using virtual reality devices to facilitate the immersion, interaction and navigation in virtual reality environments or 3D, so that greater realism is achieved by simulating the decoration as possible if to do in real life. This requires the use of 3D modeling tools like 3D Studio Max and Google Sketchup Pro that allowing exports different objects to be processed using OpenSceneGraph, which is the set of graphics libraries that handle the interaction with 3D objects and the different devices virtual reality. Very good results are obtained when test and configure machines such as virtual reality glove and the trackers, taking into account the predefined gestures easier to perform and apply thresholds to sense movement. After testing and configuring this is mapped in the application, so that the user gets the best interaction, immersion and navigation with the application.